Burnout analysis in healthcare workers. A one center cross sectional comparison between physicians, nurses, administrative positions and technicians - Rafael Jose Zamora; Sabrina Badano; María Aufiero; Patricia Martinez; Agustina Marconi (Universidad Libre, 2022)
Introduction: Healthcare workers (HCW) report higher levels of anxiety, depression, burnout, compared to the general population. The severe global health crisis caused by the coronavirus SARS-CoV-2 brought even more burden to HCW. Objective: To assessed burnout as a whole and in its different domains among HCW in a medical center Methods: We performed a cross-sectional study examining the association between demographic characteristics, healthcare position and feeling burned out. Data was collected through an anonymous online survey. We utilized the Maslach Survey for Medical Personnel in Spanish. Descriptive analyses summarized age, gender, job role, number of jobs, time in the organization and working in a COVID-19 exposed area. Ji2 tests were used to analyze association between variables and burnout. A multivariate logistic regression analysis was used to identify independent predictors of any of the burnout domains: emotional exhaustion (EE), depersonalization (DP) and/or personal accomplishment (PA). Results: 185/852 subjects answered the survey (21.7%); 79 subjects reported EE (42.7%), 61 (32.9%) DP and 31 (16.7%) PA; 98 (52.4%) had at least one component of high burnout for the dimensions analyzed. Logistics regression shows that female gender (OR= 2.21; 95% CI: 1.12-4.39), administrative positions (OR= 18.61; 95% CI: 4.28-80.93), physicians (OR= 13.27; 95% CI 3.55-49.86), and nurses (OR= 6.55; 95% CI: 1.58-27.14) were strongly associated with the presence of any burnout domain. Conclusions: The overall burnout prevalence was in range with international studies. Female workers, administrative positions, physicians and nurses were identified as independent predictors of burnout.